2011
DOI: 10.1093/jxb/err338
|View full text |Cite
|
Sign up to set email alerts
|

A rice orthologue of the ABA receptor, OsPYL/RCAR5, is a positive regulator of the ABA signal transduction pathway in seed germination and early seedling growth

Abstract: Abscisic acid (ABA) is a phytohormone that positively regulates seed dormancy and stress tolerance. PYL/RCARs were identified an intracellular ABA receptors regulating ABA-dependent gene expression in Arabidopsis thaliana. However, their function in monocot species has not been characterized yet. Herein, it is demonstrated that PYL/RCAR orthologues in Oryza sativa function as a positive regulator of the ABA signal transduction pathway. Transgenic rice plants expressing OsPYL/RCAR5, a PYL/RCAR orthologue of ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
200
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 252 publications
(217 citation statements)
references
References 41 publications
10
200
0
Order By: Relevance
“…Similar ABA signaling components were also identified in rice (Kim et al, 2012). Most of the reported abiotic stress-related PP2Cs, such as ABI1, PP2CA, ZmPP2C, FsPP2C1, and FsPP2C2, mediate the stress responses through the regulation of ABA signaling pathways (Gosti et al, 1999;Tähtiharju and Palva, 2001;González-García et al, 2003;Reyes et al, 2006;Liu et al, 2009).…”
Section: Ospp18 Is a Positive Regulator Of Stress Tolerance Independementioning
confidence: 58%
See 3 more Smart Citations
“…Similar ABA signaling components were also identified in rice (Kim et al, 2012). Most of the reported abiotic stress-related PP2Cs, such as ABI1, PP2CA, ZmPP2C, FsPP2C1, and FsPP2C2, mediate the stress responses through the regulation of ABA signaling pathways (Gosti et al, 1999;Tähtiharju and Palva, 2001;González-García et al, 2003;Reyes et al, 2006;Liu et al, 2009).…”
Section: Ospp18 Is a Positive Regulator Of Stress Tolerance Independementioning
confidence: 58%
“…Here, we found that OsPP18, a typical PP2C, could not interact with SAPK2 ( Fig. 8A; a component of ABA signal transduction in rice identified by Kim et al [2012]) or other SAPKs in rice. Meanwhile, the expression of OsPP18 was not induced by ABA (Fig.…”
Section: Ospp18 Is a Positive Regulator Of Stress Tolerance Independementioning
confidence: 85%
See 2 more Smart Citations
“…Since the discovery of Arabidopsis PYR/PYL/RCAR receptors, several orthologous genes had been discovered in important crops as tomato, rice, strawberry and soybean (Sun et al, 2011, Chai et al, 2011, Kim et al, 2012, Bai et al, ! 28 2013.…”
Section: Pyr/pyl/rcar Aba Receptors In Solanum Lycopersicummentioning
confidence: 99%